Green Fuel Innovation: Enhancing Biodiesel Production with MCM-41 Mesoporous Silica Catalysis - Hiba Ismaeel; Talib Albayati; Hayder Dhahad; Farah Al-Sudani; Issam Salih; Sohrab Zendehboudi (Journal of Applied Sciences and Nanotechnology, 2024)
In this study, mesoporous silica nanoparticles (MSNs) with a hexagonal structure and large surface area were synthesized via a sol-gel method. The properties of the synthesized MCM-41 catalyst were characterized using BET, EDX, XRD, and FTIR analyses. The results showed that the MCM-41 had a high surface area of 966 m2/g and large pore volume of about 0.91 cm3/g. Sunflower oil was converted to biodiesel in a batch reactor at different temperatures (40, 50, 60 °C), methanol-to-oil molar ratios (6:1, 9:1, 12:1), catalyst loadings (0.7, 0.9, 1.25 wt%), and reaction times (up to 80 min) using the prepared catalyst under atmospheric pressure. The biodiesel yield was found to reduce when the reaction time exceeded 1 hour despite maintaining the catalyst. The maximum biodiesel yield of 45% was obtained under optimal conditions of a 9:1 methanol-to-oil ratio, 1.25 wt% catalyst loading, 60 °C temperature, and 60 min reaction time. GC-MS analysis characterized the biodiesel composition and properties. The synthesized biodiesel showed improved properties compared to conventional fuels, with linoleic acid methyl ester (C17H34O2, 25.93%) as the main component. The MCM-41 catalyst exhibited remarkable catalytic activity and could be recovered, regenerated, and reused, reducing reaction costs. This makes it a potential alternative to homogeneous catalysts that complicate product separation.